Growth and morphological features of locally isolated microalgae Cyclotella and Pavlova - Azaman, Siti Nor Ani; M. Yusoff, Fatimah; Abd Rahim, Nur Maisarah (Institut Biosains, Universiti Putra Malaysia, 2023)
Microalgae are a vast class of simple unicellular or multicellular autotrophic life forms with non-complex growth demands. Two factors that are important in preliminary assessments of microalgae are their growth profile and morphological characteristics. This study aimed to analyze the growth profile and the morphological characteristics of two local microalgae; Cyclotella meneghiniana and Pavlova noctivaga.Both microalgae were grown in Bolds Basal Medium (BBM) with 10 inoculation and incubated at constant room temperature (25±1 °C) under the light (100 ¼mol photons m-1 s-1) in a 12h dark/12h light cycle for 21 days. Growth parameters such as specific growth rate and generation time were determined and their morphological feature was investigated using a light microscope and scanning electron microscope (SEM). From this study, C. meneghiniana showed 0.811 day-1 specific growth rate and 0.854 day-1 generation time, while P. noctivagashowed specific growth rate and generation time at 0.506 day-1 and 1.37 day-1, respectively. Preliminary morphological characterization using a scanning electron microscope for P. noctivaga showed a spherical shape with two unequal flagella. Meanwhile, C. meneghiniana showed a cylindrical shape under the light microscope. Besides, there are 12 radiating striae with indistinctive fultoportula in the center region, at both ends of the Cyclotella cell which was clearly seen under the scanning electron microscope. The information gained from the growth profiling study such as the growth rate, doubling time, specific growth rate and the morphology of the microalgae can be used and manipulated for future research.